2011
DOI: 10.1007/s00167-011-1721-8
|View full text |Cite
|
Sign up to set email alerts
|

MRI graduation of osseous reaction and drill hole consolidation after arthroscopic Bankart repair with PLLA anchors and the clinical relevance

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Previous studies have demonstrated that it is possible to indirectly estimate the osseous integration of biocomposite implants using MRI [30,33,34]. The narrowing of the tunnels on MRI, from the point of view of the authors, may only have arisen because of true osseous ingrowth in the implants, as this already demonstrates an osseous integration of the anchors.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated that it is possible to indirectly estimate the osseous integration of biocomposite implants using MRI [30,33,34]. The narrowing of the tunnels on MRI, from the point of view of the authors, may only have arisen because of true osseous ingrowth in the implants, as this already demonstrates an osseous integration of the anchors.…”
Section: Discussionmentioning
confidence: 94%
“…To our knowledge, no long-term studies are available of drill-hole changes where CT images were used to classify the degree of bony healing, and therefore the results of the present study are difficult to compare with previously published work. Using MRI scans, Stein et al 32 found evidence of drill-hole consolidation at the drill-hole sites of PLLA anchors 3 years after arthroscopic Bankart repair. Barber et al, 2 examining CT scans, found fibrous healing at the drill-hole sites of PLLA interference screws 5 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previously published work of the same patient cohort at the 7-year follow-up. 11 Stein et al 32 showed incomplete healing of drill holes 3 years after surgery using PLLA anchors. Elmlund et al 10 found that 24% of drill holes had not healed at 8 years after arthroscopic Bankart repair using PGA tacks.…”
Section: Discussionmentioning
confidence: 99%
“…20 The literature remains contradictory (with some of these studies utilizing in vitro or animal models) when determining the clinical relevance of potentially heightened inflammation and foreign body reaction secondary to absorbable poly- l -lactic acid–derived implants, which seem to have varying propensities to elicit an inflammatory response based on their composition. 21-25…”
Section: Discussionmentioning
confidence: 99%
“…20 The literature remains contradictory (with some of these studies utilizing in vitro or animal models) when determining the clinical relevance of potentially heightened inflammation and foreign body reaction secondary to absorbable poly-l-lactic acid-derived implants, which seem to have varying propensities to elicit an inflammatory response based on their composition. [21][22][23][24][25] To date, this technique has been performed in a small series by the authors for revision lateral ankle stabilization or for primary lateral ankle stabilization in larger patients with significant instability. All patients had returned to meaningful weight-bearing activities at early follow-up without recurrent instability or pain.…”
Section: Techniquementioning
confidence: 99%